EVALUATION OF THE “POLICE GOES TO SCHOOL” CAMPAIGN IN CENTRAL JAVA BASED ON KIRK PATRICK’S RULE - Christa Vidia Rana Abimanyu; Endang Widyorini (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2020)
This study aims to evaluate and provide input on the implementation of the